Effects world class swimmers using different muscles in the straightness backstroke kick movement - Ide, T.; Johnson, W. F.; Takise, S.; Hicks, L. R.; Inada, N.; Fujimori, H.; Fujimori, T.; Noel, A. L.; Mikish, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
In this study, we assess the effectiveness of utilizing a straight knee butterfly kick for world class backstroke swimmers measuring the time, max speed, and distance per stroke. We analyzed freestyle kick of knee angles from 7 times Olympic medalist, 1970`s S-shaped pulling pattern stroke with a bending knee freestyle kick. The straightness knee kick used in butterfly competitions resulted in improvements from 54.74 to 51.00in men`s 100-meter butterfly and 24.01 to 23.46 in men`s 50-meter butterfly. Using a straightness knee kick in backstroke competitions resulted in improvements from 1:01.74 to 1:00.55in the women`s 100-meter backstroke event. Increases in performance speed, max speed and distance per stroke among 9 world class elite swimmers are highly correlated to duration of the kick resistance, and straightness knee kick in backstroke. The straightness knee backstroke kick also resulted in an increase in lactate acid.